Yisaipu® Provide AS Patients With an Economical Therapeutic Option While Original Biologicals are More Advantageous in the COVID-19 Epidemic Situation - Lu, Hongjuan; Wang, Yuanqiong; Wang, Xiuwen; Wu, Xin; Zhou, Ling; Lin, Li; Sheng, Rong; Tian, Haoran; Li, Ting; Xu, Huji (Frontiers in Pharmacology, 2021)
Abstract Objectives Biologicals are the most effective treatment for ankylosing spondylitis (AS) at present. Biosimilars have entered China’s national medical insurance catalog for more than 10 years and been used widely in clinical practice because they greatly reduce the economic burden of many patients. A summary of the characteristics of AS patients receiving biologicals or biosimilars would help better understanding of their advantages and disadvantages. Knowing that the COVID-19 epidemic outbreak has produced some impact on the pattern of medical consultation in some patients, we investigated the impact of the epidemic through telephone interviews with AS patients. Methods AS patients who received biologicals or biosimilars in our department for more than one year were included in our study. General data, demographic characteristics, disease activity, quality of life and medical compliance were collected and analyzed. The patients were followed up through telephone interviews from April 20th to 27th, 2020 about the overall impact of the COVID-19 epidemic. Results There was no significant difference in Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Ankylosing Spondylitis Disease Activity Score-CRP (ASDAS-CRP) between the two groups. Health Assessment Questionnaire for Spondyloarthropathies (HAQ-s) showed that biosimilar group was superior to biological group in terms of eating, gripping and desk job. In addition, the medical cost of biosimilars was lower than that of biologicals. The overall impact of the COVID-19 epidemic on patients of biological group was comparatively smaller than that on biosimilar group. Conclusions Biosimilars provide AS patients with a safe, effective and economical selection, while biologicals have certain advantages in the COVID-19 epidemic setting, including a longer time interval between two drug administrations and the self-injection dose form of medication.